(7b-4)(7b+7)=

Simple and best practice solution for (7b-4)(7b+7)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (7b-4)(7b+7)= equation:


Simplifying
(7b + -4)(7b + 7) = 0

Reorder the terms:
(-4 + 7b)(7b + 7) = 0

Reorder the terms:
(-4 + 7b)(7 + 7b) = 0

Multiply (-4 + 7b) * (7 + 7b)
(-4(7 + 7b) + 7b * (7 + 7b)) = 0
((7 * -4 + 7b * -4) + 7b * (7 + 7b)) = 0
((-28 + -28b) + 7b * (7 + 7b)) = 0
(-28 + -28b + (7 * 7b + 7b * 7b)) = 0
(-28 + -28b + (49b + 49b2)) = 0

Combine like terms: -28b + 49b = 21b
(-28 + 21b + 49b2) = 0

Solving
-28 + 21b + 49b2 = 0

Solving for variable 'b'.

Factor out the Greatest Common Factor (GCF), '7'.
7(-4 + 3b + 7b2) = 0

Factor a trinomial.
7((-1 + -1b)(4 + -7b)) = 0

Ignore the factor 7.

Subproblem 1

Set the factor '(-1 + -1b)' equal to zero and attempt to solve: Simplifying -1 + -1b = 0 Solving -1 + -1b = 0 Move all terms containing b to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -1b = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -1b = 0 + 1 -1b = 0 + 1 Combine like terms: 0 + 1 = 1 -1b = 1 Divide each side by '-1'. b = -1 Simplifying b = -1

Subproblem 2

Set the factor '(4 + -7b)' equal to zero and attempt to solve: Simplifying 4 + -7b = 0 Solving 4 + -7b = 0 Move all terms containing b to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -7b = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -7b = 0 + -4 -7b = 0 + -4 Combine like terms: 0 + -4 = -4 -7b = -4 Divide each side by '-7'. b = 0.5714285714 Simplifying b = 0.5714285714

Solution

b = {-1, 0.5714285714}

See similar equations:

| X^2=-6-2x | | 6x(4x+2)= | | Y-8=-24 | | 17g+4g+g-22g+g=20 | | -10n+2(-2-9n)= | | .25(8z-4)=z+8 | | 1+8r=8+7r | | 2y+6=3(4y-5) | | N-14=3h | | 6v+9=3(v+8) | | 4(X-4)=0v | | -100=-4g | | 2h-h+3h-3h=13 | | 3(n+8)=22+8n | | X^2+88=10x | | 4x+3(x+4)=-9 | | -4(x-5)=9x+33 | | 6(ab)3= | | -7(n-6)-3n= | | 4+5=-8 | | -7v+4(v+3)=21 | | 15=x+ax | | 4x-48=-5(x+6) | | 9j-2j-4j=15 | | X^2=16x-65 | | 9n^2-2n+6=3 | | 19v+6b= | | 3(k+4)-6k+4+4= | | y=25x^2+20x+4 | | -7v+4(u+3)=21 | | -7y-26=23 | | 8+84p=6+10p |

Equations solver categories